Tratamento de efluente têxtil utilizando a técnica de adsorção em casca de café - Santos, Danilo Fernandes dos (2013)
The textile industry consumes a very large volume of water in the step of processing the fabric, and may also be called dyeing. In this phase is carried out dyeing step in which water is indispensable for solubilization and transport of the dye to the fibers. The wastewater from this process have strong coloration and high concentrations of COD, among other problems, can not be disposed in river networks, because thereby contaminate huge volume of water causing a major environmental problem. Many works are geared for this area in order to present a new method for the treatment of such effluent. This study aimed to evaluate the adsorption method for treating textile effluents using the coffee husk as adsorbent. This method was analyzed by changing some variables, such as pH, temperature, and agitation, setting adsorbent 1.5% (m / v), in order to find the optimum conditions for adsorption. There was a 12.04% increase in the final COD in the process due to leaching of organic material for the husk after the effluent. It was observed that the best discoloration occurred at pH 3, 230 rpm at 45°C, and 60.4% removal of dye, equilibrium was reached after 30 hours of adsorption. The model that best fit the data in the optimum process conditions was the Freundlich, presented kinetic pseudo second-order, thus characterizing the adsorption of the dye red Tiafix ME6BL in coffee husk is a process of physical nature, multilayer.